The Effects of General Anesthesia on Infants and Children's Later Development: A Comprehensive Systematic Review - Nugroho, Rio Kristian; Lestari, Sri (CV. Global Health Science Group, 2024)
The relationship between pediatric neurodevelopment and general anesthesia has been the subject of numerous investigations, yet consensus remains elusive. Objective: This review aims to explore the connection between anesthesia and child development. We conducted a thorough search of Google Scholar, PubMed, and ProQuest databases from January 2000 until March 2024, using relevant search terms such as “Adolescent,” “Anesthesia, General/ adverse effects,” “Child,” “Child Development / drug effects,” and “Preschool” resulted in 40 out of 1572 studies for reviewed. The review focused on assessing the impact of general anesthesia on children's development, excluding studies involving children with significant comorbidities or lacking unexposed controls. Two coders independently evaluated the studies, adhering to Preferred Reporting Items for Systematic Reviews criteria. Our analysis of 40 primary studies unveiled a broad spectrum of outcomes regarding the impact of general anesthesia on infants and children's subsequent development. Across cognitive domains, anesthesia altered academic achievements, IQ, and language proficiency. Sensory responses were diverse, with anesthesia affecting manual dexterity, balance, and sensory performance uniquely. Psychosocially, it influenced behavior, social skills, and neuropsychological disorders, while neurodevelopmental concerns were also identified. In summary, the effects of general anesthesia on various developmental domains underscore the need for cautious consideration in medical practice. This review revealed cognitive decline, diverse sensory impacts, and increased behavioral issues, anxiety, and neurodevelopmental disorders associated with general anesthesia. Understanding these effects is crucial for implementing effective prevention and management strategies to mitigate long-term complications.